2005
DOI: 10.1073/pnas.0409786102
|View full text |Cite
|
Sign up to set email alerts
|

A Mendelian locus on chromosome 16 determines susceptibility to doxorubicin nephropathy in the mouse

Abstract: The development of kidney disease is influenced by both genetic and environmental factors. Searching for models of glomerulopathy that display strong gene-environment interaction, we examined the determinants of anthracycline-induced nephropathy, a classic, strain-dependent experimental model applied to rodents in the past four decades. We produced three crosses derived from mice with contrasting susceptibility to doxorubicin (DOX) nephropathy and, surprisingly, we found that this widely studied model segregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 33 publications
3
90
0
Order By: Relevance
“…In recent preliminary studies, we also found that our transgenic mice are susceptible to puromycin injury, so it is likely that increased podocyte COX-2 expression may predispose podocytes to a variety of injury. Recent studies suggested that susceptibility to Adriamycin nephropathy in mice may link to a gene locus on chromosome 16 (31). Although this locus is distinct from the COX-2 gene, which is found on chromosome 1, when the specific predisposing gene products are identified, it would be interesting to investigate potential interactions with COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In recent preliminary studies, we also found that our transgenic mice are susceptible to puromycin injury, so it is likely that increased podocyte COX-2 expression may predispose podocytes to a variety of injury. Recent studies suggested that susceptibility to Adriamycin nephropathy in mice may link to a gene locus on chromosome 16 (31). Although this locus is distinct from the COX-2 gene, which is found on chromosome 1, when the specific predisposing gene products are identified, it would be interesting to investigate potential interactions with COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…After 3 days of VPA treatment the urinary podocin mRNA level has already dropped significantly compared with that of the ADR group. (#P Ͻ 0.001; **P Ͻ 0.01) BASIC RESEARCH www.jasn.org thelium in proteinuria 34 in a less susceptible mouse strain 35 requiring a high ADR dose. Besides glomerular apoptosis, podocytes can be lost in the urine because of detachment.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that distinct substrates are methylated in different fashions by this enzyme. A study that focused on identifying loci that impart susceptibility to drug-induced nephropathy has implicated PRMT7 as a candidate (Zheng et al, 2005). Also, PRMT7 plays a role in male germline imprinted gene methylation through its interaction with CTCFL (a protein that associates with the imprinting control region) and subsequent methylation of histone 4 Arg3 (Jelinic et al, 2006).…”
Section: Prmt7mentioning
confidence: 99%